Geological Structure of the Sylmar Basin: Implications for Slip Distribution Along the Santa Susana/Hospital and Mission Hills Fault System in the San Fernando Valley, CA, U.S.A. - Levy, Yuval; Rockwell, Thomas; Minas, Shant; Hughes, Alex; Rood, Dylan (Frontiers in Earth Science, 2021)
We developed a forward model using the Trishear module in MOVE to better understand the structure of the northwestern San Fernando Valley and the relationship between the Santa Susana, Mission Hills and Northridge Hills faults. This study was motivated by previous work that inferred a high slip rate on the Santa Susana fault, which is in apparent contrast to the lack of significant geomorphic expression of the fault in the Sylmar Basin region. We trenched the Mission Hills anticline from the crest to the base of slope and demonstrate that the Mission Hills anticline is an actively growing fault propagation fold. The associated thrust tip is either deeper than 15 m or sufficiently far to the south that the fault was not encountered in large diameter borings, but the minimum structural relief across the Mission Hills fault since the late Pleistocene is on the order of 37 m, suggesting a minimum uplift rate of 0.5 mm/yr. Our work presents a structural analysis that demonstrates how the Santa Susana fault system evolved in time, with the frontal thrust progressively migrating southward to the Mission Hills fault, and to the Northridge Hills blind thrust.